The player's power to change the game : ludic mutation - Schleiner, Anne-Marie, 1970- (MediaMatters., 2017)
In recent decades, a closer relation has arisen between games and activism, between games and war, between games and the city - what can be called as a gamification of certain regions of the world. What is the power of the game over life? Often the game imposes a kind of subjectification. The game's rules demand reflexive acts from the player. The player engages with the game's pre-programmed interactions, losing minutes and hours to the fascination of overcoming the challenge. And yet players also design and play their own games, thereby seizing back some of that which was lost to the game's digital regime. My underlying concern in this book is this power grab from the game. I understand these acts as player-driven transformation of an existing game into another, as a transformative process I refer to as ludic mutation. The remaker of games sees the world not as a given, fixed place composed of static objects, but as play material, to be reconfigured. Over the course of this writing, I investigate these player-driven changes to the game at varied scales and points of intervention, across gaming culture, in unique online communities of players, among artists, activists, and situated within the city - both in the digital game city and the augmented, mixed reality city.